Role of grain boundaries in the diffusion of hydrogen in nickel base alloy 600: Study coupling thermal desorption mass spectroscopy with numerical simulation. (15th October 2016) - Hurley, Caitlin; Martin, Frantz; Marchetti, Loïc; Chêne, Jacques; Blanc, Christine; Andrieu, Eric
Abstract: The role grain boundaries play in the diffusion of hydrogen in polycrystalline alloys has long been debated. Some researchers have found that grain boundaries have an accelerating effect on the transport of hydrogen across a metal membrane, while others have stated this network of sites may slow the diffusion of hydrogen or have a mixed effect depending on grain size and orientation. Thermal desorption mass spectroscopy (TDS) was used to study the diffusion of deuterium, from 294 K to 550 K, in model single crystal and polycrystalline nickel base alloy, alloy 600, having a grain size of several tens of micrometers. Using a numerical routine, solving Fick's second law of diffusion, TDS spectra were fit or simulated. The derived diffusion constant parameters ( D 0 = (1.0 ± 0.5)·10 −2 cm 2 s −1 and E D = (45 ± 4) kJ mol −1 ) for the polycrystalline alloy adequately predict and simulate the deuterium desorption from the single crystal during TDS testing. Furthermore, in the temperature range and for the grain size studied no significant effect of grain boundaries on the diffusion of deuterium in alloy 600 was observed. Consequently, the measured diffusion parameters are representative of interstitial diffusion in the alloy. Highlights: 2 H diffusion in polycrystalline and single crystal A600 was studied from 295 to 800 K. The polycrystalline A600 material had grain sizes ranging from 68 to 127 μm. The 2 H diffusion coefficient was measured by coupling TDS and numerical simulation. GBs can be neglected when modeling 2 H diffusion in the studied material and T range.